Pemanfaatan ragi (Saccharomyces cerevisiae) pada formulasi pakan dalam meningkatkan pertumbuhan ikan Nila (Oreochromis niloticus) - Rajagukguk, Bulfrit B.; Lumenta, Cyska; Mokolensang, Jeffrie F. (e-Journal BUDIDAYA PERAIRAN, 2017)
The purpose of this research was to determine the effect of yeast (Saccharomyces cerevisiae) with different composition of 5%, 10%, 15%, 20%, and without yeast in feed formulation on growth of tilapia (Oreochromis niloticus). The experimental fish used in this study had an average lengths of 2-3 cm  and weight of 1.0 g.  This research used cage measuring 100 x 100 x 100 cm3 that was placed in outdoor concrete pond of 3.5 x 5 m2.  Each cage filled with 10 fishes with three replication.  The dose given to the fish was 10% of the weight of biomass.  The fish was fed for three weeks, 3 times a day at 08.00 am, 12.00 pm, and 16.00 pm.. Research results showed that the greatest growth was achieved in fish treated 20% yeast and the lowest was observed in control fish (without yeast). Based on statistical analysis, all treatment displayed similar effect on all growth parameters.Keywords: Fish feed, Saccharomyces cerevisiae, yeast, Nile tilapia, fish growth